PENGARUH KECERDASAN EMOSIONAL,KARAKTERISTIK PEKERJAAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BPJS KESEHATAN CABANG LHOKSEUMAWE - Faisal Bukit (Universitas Islam Islam Sumatera Utara, 2020)
Increasing times require organizations to be able to make decisions in terms of the right strategy in order to compete at an increasingly stringent and competitive institution level. The decision concerns decisions in all functional areas. One thing that must be considered by the company in managing functions: -The function of management is how to manage human resources to be able to improve performance. The success and performance of agencies can be seen from the performance that has been achieved by its employees, therefore agencies demand that agencies be able to display optimal performance because of the good and bad performance achieved by employees will affect the performance and success of the agency as a whole. The performance of Lhokseumawe Branch Social Security Organizing (BPJS) employees can also be measured through the effective and efficient completion of their duties and carrying out their roles and functions and these are all linearly related and positively related to the success of an agency. There are negative factors that can reduce employee performance, including the decline in employee performance due to lack of employee emotional intelligence in completing work so that every job is always done based only on obligations so that every problem of being worked always cannot be overcome but immediately surrendered and was not done for reasons of not understanding, another thing was the lack of employee desire to explore every job because the characteristics of the work were not studied by employees of the Social Security Organizing Agency (BPJS) of the Lhokseumawe Branch Health added by the low motivation of employees to learn every job. All of that is the cause of the decline in employee performance at work. The location of the research will be conducted at the Health Insurance Provider Agency (BPJS) of the Lhokseumawe Health Branch at Jalan Iskandar Muda no 1 Kampung Lama Lama. With the sampling technique in total sampling or census method, the sample in this study amounted to 58 people in all populations. There is a significant influence of Emotional Intelligence on the performance of employees in the Health Insurance Organizing Agency (BPJS) Lhokseumawe Branch of 0.088 on employee performance so that it can be concluded that adequate Emotional Intelligence can determine employee performance will also be high even though there are other variables that support to see the results of performance an employee. There is an influence that the Job Characteristics on performance in the Health Insurance Provider Agency (BPJS) of the Lhokseumawe Branch of 0.014 can be concluded that the Job Characteristics will be able to have high results if the employee has good Job Characteristics. Employee motivation has an effect on employee performance by 0.887 and this significant indicates that motivation can improve performance, Emotional Intelligence, Job Characteristics and Motivation together have a significant effect on employee performance in the Health Insurance Administering Agency (BPJS) Lhokseumawe Branch, is 85% while the remaining 15% is explained by other variables not included in this research model.